Counseling students' experiences and interpretations of purpose development. Issue 3 (March 2023) - Sharma, Gitima; Yukhymenko-Lescroart, Mariya; Bernal-Arevalo, Katherine
Abstract: The aim of this study was to explore the lived experiences of counseling students regarding their development of sense of purpose in life and further seek their recommendations for fostering sense of purpose within educational settings. In this study, we have used pragmatism as our research paradigm and Interpretative Phenomenological Analysis (IPA) as our data analysis approach to gain deeper insights into the phenomenon of purpose development and further use the findings of this study to suggest specific purpose-strengthening educational approaches. Based on the interpretative phenomenological analysis, we identified five themes that revealed purpose development as a non-linear process that involves exploring, engaging with, reflecting upon, articulating, and actualizing one's purpose, and is influenced by both internal and external factors. In light of these findings, we discussed implications for counselor education programs that aspire to cultivate counseling students' sense of purpose in life as an important dimension for their personal wellness, which research has shown could further promote their professional development and career success.